Pathogenesis of non-alcoholic fatty liver disease and implications on cardiovascular outcomes in liver transplantation - Maliakkal, Benedict J. (Translational Gastroenterology and Hepatology; Vol 5 (July 2020): Translational Gastroenterology and Hepatology, 2019)
Along with the obesity epidemic there has been a major increase in non-alcoholic fatty liver disease (NAFLD) prevalence, paralleling a steady increase in cirrhosis of the liver and hepatocellular cancer (HCC) related to NAFLD. Currently, NAFLD (related HCC and cirrhosis) is the second most common cause for liver transplantation (LT) and it is projected to take the top spot in the next 3–5 years. Patients with NAFLD cirrhosis and HCC have a unique set of comorbidities which potentially increases their risk for cardiovascular disease (CVD) and mortality. However, a review of the published data in NAFLD patients who undergo LT, does not paint a clear picture. While CVD is the most common cause of non-graft related mortality over the long-term, the short and intermediate-term survival post LT in NAFLD cirrhosis appears to be on par with other etiologies when age and comorbidities are factored. The cardiovascular complications are increased in the immediate post-transplant period but there is a shift from ischemic complications to arrhythmias and heart failure (HF). NAFLD recurs in 80–100% patients and occurs de novo in about 50% after LT, potentially impacting their long-term morbidity and mortality. This review summarizes the available data on CVD in NAFLD patients before and after LT, explains what is currently known about the epidemiology and pathogenesis of CVD in NAFLD and posits strategies to improve wait-list and post- transplant survival.